PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV MIM AL MUTTAQIEN - Karnia, Fita Tri; Suryawan, Ari (Jurnal Pendidikan Dasar, 2024)
This research aims to determine the effect of the Think Talk Write (TTW) learning model on the learning outcomes of class IV Pancasila Education at MIM Al Muttaqien. This research is quantitative research using a pre-experimental design research method with one group pretest-posttest. The population in this study were all class IV students at MIM Al Muttaqien. The data collection technique in this research uses multiple choice questions as an instrument. To test the hypothesis, a significance value (2 tailed) of 0.000 is obtained, which means it is less than the significance level (α) of 0.05, so Ho is rejected. This means that there is a significant difference between the pretest and posttest. From these results it can be seen that the t count has a negative value, namely – 8.906, which means the average pretest score is lower than the average posttest score. Based on these data, it can be concluded that "There is an influence of the Think Talk Write (TTW) learning model on the Pancasila Education learning outcomes for class IV MIM Al Muttaqien".